ACCOUNTABILITY OF DISCRETION ACT BY GOVERNMENT OFFICIALS IN THE PERSPECTIVE OF STATE LAW OF WELFARE - Asmak Ul Hosnah; Edi Rohaedi (UNIVERSITAS PAKUAN, 2020)
Accountability of government officials' actions is strongly related to the exercise of government authority. In carrying out duties to realize the general welfare, the authority used by organs or government officials is based on the provisions of the laws and regulations (the principle of legality). However, it is not uncommon for the task to be carried out based on discretionary authority. The freedom of government officials to make decisions based on discretionary authority has a great potential to be abused which results in consequences from both point of view of administrative law as well as of criminal law. In the practice, there is discrepancy among law enforcers on the understanding of the principles related to the accountability of discretionary authority held by government officials.